OCCUPATIONAL HEALTH AND SAFETY PROCEDURES FOR EMPLOYEES IN THE DEPARTMENT OF DESIGN AND CONTRUCTION AT PT PUPUK ISKANDAR MUDA KRUENG GEUKUH NORTH ACEH - Likdanawati; Sutriani; Rahmaniar; Hamdiah; Syifa Thahira Yusral (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
PT Pupuk Iskandar Muda is a company operating in the petrochemical industry, this company is a state-owned company that produces various types of fertilizer including urea prill and urea granule. PT Pupuk Iskandar Muda is a company operating in the urea fertilizer industry. PT PIM is the first urea fertilizer factory in Indonesia which was built by Indonesian sons and daughters through the national contractor PT Rekayasa Industri. PT Pupuk Iskandar Muda has established the best possible K3 system, because the company is aware of the importance of occupational safety and health within the company. Occupational Health, namely: a science whose application is to improve the quality of life of workers through improving health, preventing work-related diseases which is realized through health checks, treatment and nutritious food intake. Occupational safety can be said to be the science and application relating to machines, work tools, materials and processing processes, the basis of the workplace and work environment as well as ways of carrying out work to ensure the safety of workers and company assets to avoid accidents and other losses. Occupational safety and health are conditions in work that are healthy and safe, both for the job, the company and for the community and environment around the factory or workplace. After carrying out Field Work Practice activities in the Design and Build Department at PT Pupuk Iskandar Muda, it can be concluded that the implementation of occupational safety and health (K3) is very necessary because it concerns the company and its employees. The implementation of K3 also has correct procedures that must be followed in accordance with statutory regulations. The procedures used at PT Pupuk Iskandar Muda, especially the Design and Build Department, in implementing Occupational Health and Safety (K3) for employees are based on Government Regulations in article 6 Number 50 of the Year 2012.